Документаційне забезпечення оформлення відпусток відділу кадрів - Маїк, Ірина; Сєров, Юрій (Видавництво Львівської політехніки, 2013)
The article considers important problem of the automation of employee vacations accounting process in HR department.
Keywords: відділ кадрів; відпустка; кадрова політика; PersonPro